Agrophysical Characteristics of the Soil of the Experimental Field - Odiljonovich, Tursunov Khayrullo; qizi, Akhmatova Rozigul Ulugbek (International Journal on Orange Technologies, 2023)
Currently, a number of scientific researches are being conducted in the world to analyze the agrochemical, agrochemical and microbiological properties of soils, the state of humus, and the interrelationship of soil biological activity with external environmental factors.